Correlations between short-course triathlon performance and physiological variables determined in laboratory cycle and treadmill tests - Zhou, S.; Robson, S. J.; King, M. J.; Davie, A. J. (The Journal of Sports Medicine and Physical Fitness, 1997)
The aim of this study was to investigate the relationships between physiological variables measured in graded cycling (CM) and treadmill running (RM) maximal tests and the performance of a short-course triathlon (1 km swim, 30 km cycling and 8 km running) in recreational triathletes. Ten male athletes with mean (+/-SD) age of 27.4(+/-5.7) years and maximal oxygen consumption (VO2peak) of 63.3(+/-8.95) mL.kg-1.min-1 participated in the study. The results showed that the VO2peak and VO2 at ventilatory threshold (VO2VT) determined in CM were significantly correlated to the overall and running times of the triathlon (r = -0.64 - 0.77, p < or = 0.05). The VO2peak and VO2VT determined in RM were also correlated to the running time when expressed as mL.kg-1.min-1 (r = -0.73, p < or = 0.05). The VT expressed as %VO2peak in both tests showed no significant correlations to triathlon performance. It appears that it is the absolute aerobic capacity of these athletes being critical to maintain a high exercise intensity in the triathlon, especially during the running segment. The mean heart rate (HR) measured in four subjects during the cycling and running segments of the triathlon was similar to the HR at VT determined in CM, which indicated that these athletes could maintain an exercise intensity close to the VT level during the competition. There was no significant correlation found between the swimming time and physiological variables measured in the laboratory cycling and running tests, which could be explained by the specific skills and economy of movement required in these exercises.